Rapid thermal annealing: An efficient method to improve the electrical properties of tellurium compensated Interfacial Misfit GaSb/GaAs heterostructures. (December 2015) - Aziz, Mohsin; Felix, Jorlandio F.; Jameel, Dler; Al Saqri, Noor; Al Mashary, Faisal S.; Alghamdi, Haifaa M.; Albalawi, Hind M.A.; Taylor, David; Henini, Mohamed
Abstract: The effect of thermal annealing on Te compensated Interfacial Misfit GaSb/GaAs heterostructures is investigated by using two different thermal annealing procedures, namely rapid thermal annealing and furnace annealing. The electrical properties of the devices are studied by using Current–Voltage, Capacitance–Voltage and Deep Level Transient Spectroscopy techniques. It is observed that rapid thermal annealing treatment is superior in terms of improvement of the electrical characteristics compared to furnace annealing treatment. The lowest leakage current and defect concentration are obtained when rapid thermal annealing is employed. Highlights: We studied diodes based on Te-GaSb/GaAs devices grown by Interfacial Misfit Technique. The concentration of traps decreased by choosing appropriate annealing conditions. We show that possible defect compensation is observed with RTA treatments. The results showed that the annealing improves the electrical properties of devices.